Implementasi Pembelajaran Literasi Finansial di Sekolah Dasar - sani aryanto (Elementary Teacher Education Program, Majalengka University, 2023)
Financial literacy is considered a type of literacy that is expected to improve students' thinking skills in managing finances. However, financial literacy learning has not been fully integrated into intracurricular learning activities and is still implicitly. Therefore the aim of this research is to provide a comprehensive picture of the implementation of financial literacy learning in elementary schools. This research used a case study method involving 3 teachers and 90 students from 3 elementary schools, including SDN Cipayung 04 Pagi Jakarta City, SDN Perwira 01 Bekasi City, and SDN Pisangan 02 Banten City. The research results show that the implementation of financial literacy learning is implicit, although the results of the independent curriculum analysis show the existence of financial literacy learning in natural and social sciences subjects. In practice, the learning process has not been carried out explicitly and systematically in the context of intracurricular learning, whereas in extracurricular learning, financial literacy learning is implemented through the Cha-Ching program. The implementation of this program is still partial and has not been implemented in various elementary schools. Based on the results of the perception survey from class teachers, it can be seen that students are not yet able to understand the differences between wants and needs; students are also not able to classify spending priorities; and students are deemed unable to identify basic terminology related to money. Therefore, it is hoped that the results of this research will encourage teachers to develop more innovative financial literacy.